Ethical Concerns and Procedural Pathways for Patients Who are Incapacitated and Alone: Implications from a Qualitative Study for Advancing Ethical Practice - Moye, Jennifer (HEC Forum, 2017)
Adults who are incapacitated and alone, having no surrogates, may be known as “unbefriended.” Decision-making for these particularly vulnerable patients is a common and vexing concern for healthcare providers and hospital ethics committees. When all other avenues for resolving the need for surrogate decision-making fail, patients who are incapacitated and alone may be referred for “public guardianship” or guardianship of last resort. While an appropriate mechanism in theory, these programs are often under-staffed and under-funded, laying the consequences of inadequacies on the healthcare system and the patient him or herself. We describe a qualitative study of professionals spanning clinical, court, and agency settings about the mechanisms for resolving surrogate consent for these patients and problems therein within the state of Massachusetts. Interviews found that all participants encountered adults who are incapacitated and without surrogates. Four approaches for addressing surrogate needs were: (1) work to restore capacity; (2) find previously unknown surrogates; (3) work with agencies to obtain surrogates; and (4) access the guardianship system. The use of guardianship was associated with procedural challenges and ethical concerns including delays in care, short term gains for long term costs, inabilities to meet a patient’s values and preferences, conflicts of interest, and ethical discomfort among interviewees. Findings are discussed in the context of resources to restore capacity, identify previously unknown surrogates, and establish improved surrogate mechanisms for this vulnerable population.